KEPUTUSAN KONSUMEN DALAM MEMILIH HOTEL PANGERAN PEKANBARU RIAU - Dewi Titiani Riski; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Hotel is the kind of industries that produce and provide something in the form of goods and services. Thus the hotel does not only sell intangible products such as forms of services, entertainments, the comfortable, clean and easy atmosphere or environment. In order to maintain its existence, the hotel requires a good management and changes in consumer demand so as to survive and compete with other hotels.Environmental influences, individual influences and factors inherent in the hotel are intimately associated with the consumer in taking consumer interests to stay, especially those related to quality of service factors, price , location and facilities.This research used descriptive quantitative method to analyze the probloms. The sample of this research was 100 respondents which was taken by accidental sampling. The technique of collecting data in this research used observation, questionaire and interview. To know the interval range, the writer used likert scale.Key Word : Product,price,facilities and location